Design and Construction of a Biogas-Fueled Power Generator - Egi Permana (Journal of Emerging Innovations in Engineering, 2025)
This study explores the design and construction of a household-scale biogas electricity system using Cow dung in Girinata Village, Indonesia, as a practical response to energy access challenges in rural communities. Drawing on anaerobic digestion technology, the system integrates a fiber-based digester, polyethylene gas holder, and a modified dual-fuel generator to produce reliable electricity from cow manure. A qualitative case study and field experiment approach was employed to assess both technical feasibility and social acceptance. Results show the system is technically viable, economically affordable, and socially accepted, with minimal operating costs and high user engagement. Despite initial design challenges affecting gas quality, performance was stable under optimized conditions. This research contributes empirical insights to the literature on decentralized renewable energy, particularly in underrepresented tropical settings, and supports the potential for community-scale replication to promote sustainable energy transitions